Who is the effective teacher? Perceptions of early career English teachers in Israel. Issue 5 (3rd September 2021) - Carmel, Rivi; Badash, Merav
ABSTRACT: Issues of teacher quality and effectivity inform teacher education, policy, practice and research and are connected with teacher resilience and retention. (Mansfield, C.F., S. Beltman, A. Price and A. McConney. 2012. "Don't sweat the small stuff:" Understanding teacher resilience at the chalkface. Teaching and Teacher Education 28, no. 3: 357–367). Effective teachers are strongly associated with resilient teachers, those who possess particular personality traits and maintain their commitment to the job despite the challenges they face (Gu, Q. and C Day. 2007. Teachers resilience: A necessary condition for effectiveness. Teaching and Teacher Education 23, no. 8: 1302–1316). This paper examines teachers' views on the propensities of effective English as a Foreign Language (EFL) teachers and on the factors that contributed to their teacher preparation. Data was collected using a self-report online survey from 167 early career English teachers and in-depth interviews with a sample of six teachers. Results point at personal 'soft factors' such as motivation, enthusiasm and self-confidence coupled with school support, team work and shared teaching practices, seen as most cardinal in English teachers' effectivity and resilience. Programmes nurturing emotional management, self- awareness and ways of improving self-regulation are suggested both in pre-service preparation programmes and in-service professional development, in order to sustain teacher motivation and commitment.